2011
DOI: 10.3402/fnr.v55i0.7289
|View full text |Cite
|
Sign up to set email alerts
|

Cut-off scores for the Minimal Eating Observation and Nutrition FormVersion II (MEONF-II) among hospital inpatients

Abstract: Background and objectiveThe newly developed Minimal Eating Observation and Nutrition Form – Version II (MEONF-II) has shown promising sensitivity and specificity in relation to the Mini Nutritional Assessment (MNA). However, the suggested MEONF-II cut-off scores for deciding low/moderate and high risk for undernutrition (UN) (>2 and >4, respectively) have not been decided based on statistical criteria but on clinical reasoning. The objective of this study was to identify the optimal cut-off scores for the MEON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…the study can be viewed as a naturalistic study. Furthermore, the rates of moderate/high risk of undernutrition in this study is very similar to that reported in other studies using a restricted number of registered nurses for data collection [3,4] with good inter-rater reliability (kappa, 0.81) [25] in this type of patient populations. Also other aspects of our observations support accuracy of data as they replicate previous findings (see below).…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…the study can be viewed as a naturalistic study. Furthermore, the rates of moderate/high risk of undernutrition in this study is very similar to that reported in other studies using a restricted number of registered nurses for data collection [3,4] with good inter-rater reliability (kappa, 0.81) [25] in this type of patient populations. Also other aspects of our observations support accuracy of data as they replicate previous findings (see below).…”
Section: Discussionsupporting
confidence: 75%
“…This was done following each patient assessment. These questions have previously been used to assess the user-friendliness of the MEONF-II [3][4][5] .…”
Section: User-friendliness Of Meonf-iimentioning
confidence: 99%
See 3 more Smart Citations